House Prices and Monetary Policy in South Korea - Inho Song (Korea Development Institute (KDI), 2013)
- The ex-ante responses the central bank made in the past to achieve house price stability may not be as beneficial as ex-post responses. However, this attitude has been challenged after facing enormous conomic and social expenses caused by the huge economic setbacks resulting from the global financial crisis in 2008. - In the past, houses were generally regarded as a kind of durable asset from the perspective of monetary policy, and therefore changes in house prices, such as share price fluctuations, were not regarded as a factor requiring a monetary policy response. - Hit by the financial crisis resulting from the US sub-prime mortgage crisis in late 2007 and by Lehman Brothers filing for bankruptcy in September 2008, the global economy experienced a 1.6 years slowdown (December 2007 to Jun 2009), the longest the world had seen since the Great Depression in the 1930s. - The recent economic recession that occurred in relation to the housing market continued for a longer period and caused larger losses to the national economy on average than economic recessions that had nothing to do with the housing market. - Now that financial stability has been added as a new goal for the Bank of Korea (BOK), there is a greater need than ever for an analysis to be made concerning the linkages between house prices and monetary policy that takes into account recent economic conditions. - During the eighth revision of the Bank of Korea Act on Sep. 16, 2011, financial stability was declared to be a new goal for the BOK. The act was revised to say, "The Bank of Korea shall pay heed to financial stability as it carries out monetary policy." - Inspired by these factors, this paper uses model simulations to deduce the optimal monetary policy frontier line of central bank, and analyzes the effectiveness of monetary policy that takes house prices into account. - The paper discovers the mutual complementarity of housing and consumption and includes this characteristic in its design of the macroeconomic model. - Presuming there is an expectation that house prices will go up inside an economic structure where the average loan-to-value (LTV) ratio is 50%, housing and consumption act as complementary goods, and housing demand and consumption tend to move together. - The simulation shows that, assuming that the first priority of the central bank is decreasing inflation volatility and economic volatility, interest rate rules that respond to house prices contribute 6% more to inflation stability and 2% more to economic stabilization than interest rate rules that do not. - The central bank needs the ability to determine the fundamental factors affecting house prices, and if economic stability is considered an important task, interest rate rules that respond to house prices will effectively carry out monetary policy goals. - Since the central bank needs to monitor house prices for financial stability, it is necessary to reorganize credible market indices and construct statistical models to achieve monetary policy goals. - The most that is being done in South Korea at the present is using financial stability reports and other data that KB Kookmin Bank and Real Estate 114 available to the market to gather information about the housing market. - The Federal Reserve Bank of New York regularly purchases data from CoreLogic and uses it to monitor house prices. It periodically releases the results of its comprehensive analysis of the financial market in relation to house prices. - It is necessary to reorganize market indices and devise economic models in order to monitor volatility in the housing market and to conduct an empirical analysis of the effectiveness of policies. - Economic contraction that is connected with the housing market has brought more attention to the important role that monetary policy should play than ever before. - Analyzing and assessing the intrinsic value of house prices in response to an economic recession that is connected with the housing market is an important job for the central bank to do in their pursuit of new monetary policy goals. - It might be necessary to consider expansionary monetary policy that seeks to reduce the volatility in house prices and stabilize consumer sentiment about the recovery in the real economy in current situation.
Keywords: 330